2020
DOI: 10.1161/circinterventions.120.009496
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Coronary Obstruction and Feasibility of Coronary Access After Repeat Transcatheter Aortic Valve Replacement With the Self-Expanding Evolut Valve

Abstract: Background: The supra-annular leaflet position and tall stent frame of the self-expanding Evolut PRO or Evolut PRO+ transcatheter heart valves (THVs) may cause coronary occlusion during transcatheter aortic valve replacement (TAVR)-in-TAVR and present challenges for future coronary access. We sought to evaluate the risk of TAVR-in-TAVR with Evolut PRO or Evolut PRO+ THVs and the feasibility of future coronary access. Methods: The CoreValve Evolut PRO Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…Assessing the feasibility of coronary access and PCI is increasingly relevant as TAVI expands toward younger and lower-risk patients who have an increased life-time risk for repeat invasive angiography due to progression of CAD ( 9 12 ). Studies using pre or post-procedural CT to virtually assess coronary access have suggested that challenging or un-feasible cannulation may occur following 9–35% TAVR ( 16 18 ), 27–78% of TAVI-in-TAVI ( 19 , 20 , 25 ) and 58% of ViV-TAVI ( 22 ) procedures. However, data from real studies of post TAVI cannulation are more re-assuring with success rates for diagnostic cannulation and PCI success ranging between 90–100 and 92–97%, respectively, even in the acute setting ( 11 14 , 26 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Assessing the feasibility of coronary access and PCI is increasingly relevant as TAVI expands toward younger and lower-risk patients who have an increased life-time risk for repeat invasive angiography due to progression of CAD ( 9 12 ). Studies using pre or post-procedural CT to virtually assess coronary access have suggested that challenging or un-feasible cannulation may occur following 9–35% TAVR ( 16 18 ), 27–78% of TAVI-in-TAVI ( 19 , 20 , 25 ) and 58% of ViV-TAVI ( 22 ) procedures. However, data from real studies of post TAVI cannulation are more re-assuring with success rates for diagnostic cannulation and PCI success ranging between 90–100 and 92–97%, respectively, even in the acute setting ( 11 14 , 26 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…With these valve-in-valve procedures, coronary obstruction risk and access difficulty will increase. [ 88 , 89 ] Hopefully, future studies will shed light on an appropriate strategy for younger patients who have to undergo multiple such procedures.…”
Section: Future Directionsmentioning
confidence: 99%
“…Clinical, in vitro, and in silico studies have shown that the implantation of a bioprosthetic valve alters the sinus flow dynamics and may compromise or obstruct coronary access, leading to potential impairment of coronary perfusion 11–16 …”
Section: Introductionmentioning
confidence: 99%
“…Clinical, in vitro, and in silico studies have shown that the implantation of a bioprosthetic valve alters the sinus flow dynamics and may compromise or obstruct coronary access, leading to potential impairment of coronary perfusion. [11][12][13][14][15][16] The aim of this study is to evaluate the impact of various BP conditions on the coronary perfusion and hemodynamic performance after AVR. These highly controlled mechanistic in vitro studies can yield evidence supporting the potential need for revised (potentially raised) optimal BP targets in patients treated with AVR for AS compared with the general population.…”
Section: Introductionmentioning
confidence: 99%